P08.36 Chlamydia trachomatis infection in women in germany, 2008–2014. (13th September 2015) - Dudareva-Vizule, S; Jansen, K; Haar, K; Sailer, A; Hofmann, A; Hamouda, O; Bremer, V
Abstract : Background: Chlamydia trachomatis (CT) infections are not reportable in Germany and limited data on CT-prevalence among women is available. In 2008 an opportunistic CT-screening programme for women <25 years (OCS) was introduced. We assessed positivity rate of CT-infection among women and coverage of the OCS in order to develop recommendations for prevention. Methods: In September 2010 voluntary laboratory-based sentinel surveillance system was implemented and is collecting retrospective (from 2008) and prospective data on CT-tests together with information on age and test reason (TR). We calculated positivity rates (PR) by age-group and TR over years. We used Chi2 and two-sample t-test, accordingly. We estimated coverage of OCS by extrapolating the proportion of CT-tests attributable to OCS to the respective German population. Results: As of 10.04.2015 data from 24 laboratories were available for analysis. Overall 93% (3, 440, 131) of all tests (3, 701, 288) were among women. Among those 24% were attributable to OCS, 36% to screening in pregnancy, 25% to diagnostic testing, and in 15% the TR was unknown. The coverage of OCS increased over time from 8% in 2008 to 11% in 2009, and 12% in 2014. PR was highest in age-groups 15–19 (6.75%) and 20–24 (5.93%) years compared to age-groups <15 (3.38%), 25–29 (3.26%), and ≥30 (1.42%) years, p-value <0.001. PR gradually decreased from 2008 to 2014 in age-groups 15–19 (7.44% to 6.51%) and 20–24 (6.64% to 5.71%) years, p-value <0.001. Conclusion: The proportion of young women testing positive for CT is high despite gradual but slight decrease in PR among 15–24 years old women. OCS coverage in Germany is low and did not increase substantially in the last years. OCS should be promoted among the target population and physicians. Awareness campaigns for young women should be implemented. Respective regulations should be expanded and remuneration for counselling to physicians for OCS offered. Disclosure of interest statement: Chlamydia trachomatis laboratory sentinel is funded by German Federal ministry of health. No conflicts of interest.